2010
DOI: 10.2147/jaa.s13705
|View full text |Cite
|
Sign up to set email alerts
|

Updates in the treatment of ocular allergies

Abstract: Allergic diseases have greatly increased in industrialized countries. About 30% of people suffer from allergic symptoms and 40%–80% of them have symptoms in the eyes. Atopic conjunctivitis can be divided into seasonal allergic conjunctivitis (SAC) and perennial allergic conjunctivitis (PAC). The treatment of SAC is simple; antihistamines, anti-inflammatory agents, or chromoglycate. In severe cases of SAC, subcutaneous or sublingual immunotherapy is helpful. PAC needs longer therapy, often year round, with mast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…The clinical symptoms and histopathological changes in the BALB/c mice model corresponded to the immediate and late phases of the allergic process, as described in humans [18,19]. In addition to ocular disease, there was also a systemic immune response induced by the mite, characterized by an increase in both total serum and Der f -specific IgE and IgG levels and in the ratio of Th2 cytokine IL-4/Th1 cytokine IFN-γ, which parallels findings in humans [5]. The present model, as a good mimic of human AC, indicates that it is an accurate instrument for studying the pathogenesis of ocular allergy and for testing therapies for AC.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The clinical symptoms and histopathological changes in the BALB/c mice model corresponded to the immediate and late phases of the allergic process, as described in humans [18,19]. In addition to ocular disease, there was also a systemic immune response induced by the mite, characterized by an increase in both total serum and Der f -specific IgE and IgG levels and in the ratio of Th2 cytokine IL-4/Th1 cytokine IFN-γ, which parallels findings in humans [5]. The present model, as a good mimic of human AC, indicates that it is an accurate instrument for studying the pathogenesis of ocular allergy and for testing therapies for AC.…”
Section: Discussionsupporting
confidence: 55%
“…Chemotactic factors released by mast cells are responsible for accumulation of eosinophils and neutrophils at the site of allergic inflammation. Eosinophils contain granules in which preformed cytokines are rapidly secreted depending on the cytokine stimuli, T helper cell 1 [Th1; interleukin (IL)-12, IL-27 and interferon (IFN)-γ] and Th2 (IL-4 and IL-13) [5]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these patients often receive higher ESA doses [90,91,92], it is difficult to distinguish the effects of nutritional deficiency, lower pretreatment Hb levels, and delayed ESA initiation from possible racial-specific biological effects on ESA responsiveness [1, 93]. In the Procrit® Dosed Once Weekly in the Patients with Anemia due to Early Renal Insufficiency (POWER) study [94], a post-hoc analysis reported that African-American nonsmokers demonstrated a statistically significant decreased response to epoetin alfa compared with nonsmokers of other races (mean Hb at week 16: 11.61 vs. 11.86 g/dl, p = 0.02); however, whether this was a clinically significant difference in response is not known.…”
Section: Anemia Management In African-americans Through the Course Ofmentioning
confidence: 99%
“…Once dialysis is initiated, African-Americans receive higher ESA doses [90,91,92]; however, it is difficult to distinguish the effects of nutritional deficiency, lower pretreatment Hb levels, and delayed ESA initiation from possible racial-specific biological effects on ESA responsiveness. Awareness of racial-specific challenges in anemia management in addition to CKD risk factors, progression, complications, and treatment responses will help physicians serve African-American kidney patients more effectively.…”
Section: Eliminating Ethnic Disparities In Anemia and Chronic Kidney mentioning
confidence: 99%